Primary care dental professionals' experiences of sharp injuries in Qatar: A cross-sectional study - Marji, Tamara; Syed, Mohamed Ahmed (Frontiers in Oral Health, 2022)
Objectives: There are very few studies assessing sharps injuries solely in dental professionals internationally. This study aims to understand experiences of sharp injuries amongst primary care dental professionals in Qatar. Methods: A cross-sectional study was designed. Dental professionals working at Primary Health Care Corporation (PHCC), a public sector healthcare organization and Qatar’s largest primary care provider with 27 primary health care centres in Qatar were invited to participate in the study. An online questionnaire was administered to understand participants’ experience of sharps injuries and access to occupational health service and training. Findings: A total of 114 dental professionals participated in the study. 68.42 % (N= 78) participants reported experiencing a sharp injury in the 12 months prior to the survey. Majority (N=58; 75.36 %) of the reported causes of sharp injuries were related to dental explorer (N=31; 40.26 %); and dental injection needle (N=27; 40.26 %). Of those who had experienced a sharps injury, 84.47 % (N=87) did not report them. Conclusion: In conclusion the results highlight sharps injuries are common amongst primary care dental professionals and despite having good access to occupational support services, majority of the dental professionals did not report their injuries. Continuous education and training programs must be implemented to improve knowledge and raise awareness to reduce the burden of sharp injuries amongst dental professionals. More studies from other dental settings are need to improve understanding of dental professionals’ experiences of sharps injuries in Qatar and elsewhere.